GAMBARAN GAYA HIDUP SEHAT PADA KLIEN HIPERTENSI (STUDY LITERATUR REVIEW) - Diana Nur Hidayanti Tanjung; Lia Meilianingsih; Tati Suheti; Achmad Husni (Jurnal Keperawatan Indonesia Florence Nightingale, 2021)
Hypertension is a condition where a person experiences an increase in blood pressure above normal which results in an increase in morbidity and mortality / mortality. This research is motivated by the increasing incidence of hypertension in Indonesia. The incidence of hypertension in Indonesia is 34.1% which previously in 2013 amounted to 31.7%. While the incidence rate in West Java is 43%. This study aims to find a picture of "Healthy Lifestyle in Hypertension Clients". The method used is descriptive research with a literature review study approach, to identify, assess, and interpret all findings on a research topic, and answer predetermined research questions. This study uses 5 journals obtained from google schoolar related to lifestyle in hypertensive clients and then data extraction methods, data quality assessment, and data synthesis are conducted. The results of the analysis of 5 journals found hypertension sufferers have an unhealthy lifestyle. This research is recommended for health services or health centers, especially community nurses to be the basis in providing nursing interventions in increasing client targets regarding hypertension with a healthy lifestyle. Keywords: Hypertension, Lifestyle